Absenteeism of nursing professionals: Impact of COVID-19 (Research, Society and Development, 2024)
To investigate absenteeism due to illness among nursing professionals during the COVID-19 pandemic in a University Hospital in the Southern Region of Brazil, from March 11, 2019 to March 10, 2022, divided into three periods of one year each. Retrospective epidemiological research, examining documentary data from a secondary source where the occurrences of absence and the total days of absence of these professionals obtained through hospital worker health bodies were analyzed. In the first year of the pandemic, there was an increase of more than 10 thousand days compared to the previous period. Nursing Assistants had the highest average number of days absent during this period. The Medical Clinic, Surgical Center and Adult Intensive and Semi-Intensive Care Unit sectors recorded the highest number of absences in the following periods. Infectious and parasitic diseases, especially COVID-19, were the main cause of absence during the pandemic, while mental and behavioral disorders represented the highest rate of absence in number of days in the first year. Diseases of the musculoskeletal system were also among the main causes of sick leave in the period before and during the pandemic. The COVID-19 pandemic had a significant impact on absenteeism among nursing professionals in the years 2020 to 2022. COVID-19 infections were the main cause of sick leave, showing the high exposure of these professionals to the virus. There has been an increase in the number of sick days due to mental and behavioral problems, reflecting the psychological pressure faced during the pandemic. Musculoskeletal disorders were also common, highlighting the physical challenges intensified by work demands during this period.